2005
DOI: 10.1088/0034-4885/68/10/r03
|View full text |Cite
|
Sign up to set email alerts
|

Top quark physics in hadron collisions

Abstract: The top quark is the heaviest elementary particle observed to date. Its large mass makes the top quark an ideal laboratory to test predictions of perturbation theory concerning heavy quark production at hadron colliders. The top quark is also a powerful probe for new phenomena beyond the Standard Model of particle physics. In addition, the top quark mass is a crucial parameter for scrutinizing the Standard Model in electroweak precision tests and for predicting the mass of the yet unobserved Higgs boson. Ten y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 343 publications
(500 reference statements)
2
86
0
1
Order By: Relevance
“…(34). We use CTEQ parton distribution functions [28,29] Although this is not an extensive scan of the parameter space, it gives a sense of theoretical uncertainties in m Bl provided that realistic production mechanism is employed 6 . Computing the mean and the error, we arrive at the results shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(34). We use CTEQ parton distribution functions [28,29] Although this is not an extensive scan of the parameter space, it gives a sense of theoretical uncertainties in m Bl provided that realistic production mechanism is employed 6 . Computing the mean and the error, we arrive at the results shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…ATLAS and CMS plan to employ a variety of methods for measuring the top quark mass [3,4,5,6,7,8]. These methods can be divided into two classes.…”
Section: Introductionmentioning
confidence: 99%
“…For an in-depth introduction to the Standard Model, I would like to point the reader to textbooks like references [1,2,3]. Reference [4] is an overview article which focuses on top quark physics in hadron colliders.…”
Section: Chapter 2 the Top Quark In The Standard Modelmentioning
confidence: 99%
“…Afterwards the single-top production via the electroweak force is discussed in more detail. A detailed review on top quark physics can be found in reference [14].…”
Section: Production Modes Of the Top Quark In The Standard Modelmentioning
confidence: 99%